A morfologia do trabalho do professor de ciências no contexto de uma escola democrática - Rezende, Danielle Martins (2016)
This study deals with an investigation into Master's level at the Graduate Program in Education of the Federal University of Uberlândia. Aimed to describe and analyze the structure of the science teacher's work and its impact on knowledge and political and pedagogical practices in the context of the Municipal Elementary School Judge Amorim Lima, located in the city of São Paulo. The survey field school is organized from the perspective of democratic management and curriculum based on the collective construction of knowledge, as advocated by the Brazilian legislation and the school of experience Bridge (Portugal). To develop this research, we used the participant observation techniques, literature and semi-structured interviews to teachers of the institution sciences. Through the data from reality categories were extracted: "Work", "Precarious work," "Wage Labour", "Education Policy and Ideology", "Legal Framework Bourgeois of Education" and "Reality", analyzed based on dialetc method hermeneutic. The characterization of the morphology of the science teachers working in the democratic context reveals the limits and possibilities of a new configuration of the teaching practice. The reorganization guided by openness of the management provided a different conformation in the work of science teachers, which is no longer limited to the timely subject of a fragmented time and has the support of colleagues from other areas in the collective spaces of study. The dissipation of the difficulties with the collaboration of the whole school community and the fact that they put as a mediator of the teaching-learning processes allows for greater expansion and autonomy of action of these teachers within the school, but this relative autonomy, regulated by social control parameters workers as the state's evaluation mechanisms further shape and limit teaching.